(untitled) (Revista Contexto & Educação, 2022)
This article discusses the contribution of undergraduate courses at the Federal Institute Farroupilha Campus Alegrete to teacher training and how their graduates were inserted in the educational environment. The study focused on newcomers to the Licentiate Degree Courses in Biological Sciences, Chemistry and Mathematics, between the years 2010 to 2014. The research had a qualitative focus by conducting an interview with alumni working in teaching. As a result, it was found that, in these degree courses, in the period studied, PIBID, curricular internships and laboratory activities were pointed out as positive points of training. On the other hand, the weaknesses highlighted were the little regency in the classroom, late offering of Libras in the curriculum and little importance for Special Education. Therefore, the necessary resizing were listed from the discussion established regarding the offer of Libras subjects, as well as access to the content of special education, along with more time for mandatory (or optional) curricular internship practices and practices of laboratory, which were also listed as fundamental in the training process.